Realizing Africa’s Rice Promise - Wopereis, Marco C.S (CABI, 2014)
In many countries in sub-Saharan Africa (SSA), rice used to be consumed only during special events, perhaps once or twice a year. From a luxury crop it has now become the most rapidly growing food source in SSA. This is driven by many factors, including urbanization, changes in employment pat- terns, rising income levels, shifts in consumer preferences, and rapid population growth. Rice is the leading provider of food calories in West Africa and in Madagascar, and it is now the third largest source of food energy in Africa as a whole. Because of its ease of preparation, storage and cooking, low preparation costs, low price and steady supplies (often through imports), rice has become a sta- ple food for the poorest sectors of urban populations. The proportion of Africans living in urban areas is expected to continue to increase rapidly from its current (2012) level of 38% to reach 48% by 2030. The increasing trend in rice consumption across the continent is, therefore, likely to con- tinue for the foreseeable future. The increasing demand for rice means that in 2009 nearly 37% of the rice consumed in SSA was imported. This translated into imports of 9.8 million tonnes (Mt), worth more than US$5 billion. This reliance on imports is a very risky, expensive and unsustainable strategy. The risks became pain- fully clear in 2008 during food riots in major African capitals in protest against high rice prices caused by traditional exporting countries like Vietnam, India and Egypt closing their borders and banning exports. Rice is one of the most protected commodities in the world and only about 7% of global production is traded on the international market. Average rice prices in 2012 were about 2.5 times the price levels in 2000 and the rice price on the world market has seen tremendous fluctuations. Prices are predicted to remain high and volatile because of declining production capacity in major rice-producing countries in Asia as a result of increasing pressure on land and water resources and growing demand. Increasing rice prices will adversely affect poor and low-income households who spend a larger proportion of their revenue on staple food relative to high-income households. In a region where more than 40% of the population lives below the extreme poverty line of $1 a day, coping with high rice prices will mean poorer households taking measures which could include a reduction in their intake of essential nutrients, especially in urban areas, and long episodes of food deprivation and malnutrition. Moreover, in countries such as Guinea-Bissau and Sierra Leone, where annual per-capita rice consumption is above 100 kg, the incidence of higher rice prices has the potential to trigger political disturbances.